The strategic targeting of females by transnational tobacco companies in South Korea following trade liberalisation - Lee Kelley; Carpenter Carrie; Challa Chaitanya; Lee Sungkyu; Connolly Gregory N; Koh Howard K (BMC, 2009)
Abstract Background In 1988 South Korea opened its cigarette market to foreign companies under the threat of US trade sanctions. Despite strong social stigma against female smoking in South Korea, and restrictions on tobacco marketing to women and children, smoking rates among young Korean females increased from 1.6% in 1988 to 13% in 1998. Previous analyses describe how Asian countries have been targeted by transnational tobacco companies for new markets, with Asian females offering substantial future growth potential. An understanding of the strategies used by TTCs to increase smoking among Korean females is critical to public health efforts to adopt a stronger gender perspective in implementing the Framework Convention on Tobacco Control. Methods Internal documents of transnational tobacco corporations were systematically searched using keywords focused on the targeting of the female market since market liberalisation in 1988. Industry documents were analysed alongside primary and secondary data on the tobacco industry in South Korea. Results TTCs have targeted Korean females since the late 1980s, conducting market research to understand consumer preferences, cultural characteristics and social changes affecting women and girls. Brands designed to appeal to females have focused on "slim" and "superslim" cigarettes, "light" and "mild" claims, and marketing which appeals to the growing numbers of young women entering the labour force. Strategies for overcoming legal restrictions on marketing to women and children have included the use of company rather than brand names, retail distribution at venues frequented by females, trademark diversification and sponsorship. Conclusion Given the high male smoking rates in South Korea, tobacco control efforts have given limited attention to girls and women. The limited data available on female smoking behaviour suggests that, despite legal restrictions and social stigma, smoking among females has increased since market opening, notably within younger age groups. In addition to more detailed trend data, there is an urgent need for the development and implementation of gender-sensitive tobacco control measures. Part of South Korea's accession to the FCTC should include emphasis on measures to address the strategic targeting of Korean females by TTCs.